Navigating Among Slaves. The Spanish Capuchins in the Kingdom of the Congo: Faith and Diplomacy - Ruiz-Peinado Alonso, José Luis (Revista Complutense de Historia de América, 2022)
Africa’s connection with Europe and America as of the sixteenth century cannot be understood without reference to the Atlantic Slave Trade. The trade was the backbone of the wide-ranging relations and interests that were created at the time. The role of the missionaries, aside from their pastoral work, was increasingly important in the articulation of the networks of influence and pressure, as in the slave trade, that was the principal matter that moved interests on either side of the Atlantic. The Spanish Capuchin missions in the Congo fit within this context. They began in 1645 and ended in 1658. Portugal had become independent but had not yet been recognized by the Holy See nor the Spanish government, so they fell officially within the jurisdictions of the Spanish monarch, although for the Portuguese authorities they were an intrusion in their sovereignty and their spheres areas of influence. Portuguese hostility to the presence of the Spanish missionaries constituted a source of continuous problems and conflicts. These disagreements would end after the defeat of the Kingdom of the Congo in 1665, which would block the entry of more Spanish Capuchins to western central Africa.
Keywords: Western Africa; Slave trade; Capuchin missions; Embassies